Residual Pain in the Context of Selecting and Switching Biologic Therapy in Inflammatory Rheumatic Diseases - Berghea, Florian; Berghea, Camelia Elena; Zaharia, Dumitru; Trandafir, Andreea Iulia; Nita, Elena Cristina; Vlad, Violeta Maria (Frontiers in Medicine, 2021)
For many years, inflammatory rheumatic diseases (IRDs) represented a source of disappointment in medical care caused by the mediocre efficacy of the available treatments. Some of these diseases, like Rheumatoid Arthritis (RA) or Ankylosing Spondylitis (AS), caused fear in the general population, especially due to associated joint deformities and subsequent disabilities. However, in the last 20 years, a new successful class of antirheumatic drugs has become available: biologic Disease-Modifying Antirheumatic Drugs (bDMARDs). Due to this innovative treatment, the days are over when joint and spine deformities defined the condition of a person with RA or AS. Nonetheless, expectations are higher today, and other clinical problems, (not entirely solved by bDMARDs), seem to drive the drug selection during the span of rheumatic diseases. Most of these issues are covered by the term “unmet needs.” One of the most intriguing of such needs is the residual pain (RP) in patients that are otherwise in the biological remission of the disease. Present in a significant proportion of the patients that enter remission status, RP is poorly understood and managed. In recent years, new data has become available in this area and new conceptual clarifications have occurred. In this review, we explain the various nature of RP and the necessity of treatment diversification in such situations. All in all, we believe this condition is far more complex than simple pain and includes other clinical aspects, too (like fatigue or mood changes) so the terms Post-Remission Syndrome (PRS), and PRS pain might be more appropriate.